Phenotypic and genotypic characterization of linezolid resistance and the effect of antibiotic combinations on methicillin-resistant Staphylococcus aureus clinical isolates - Asmaa I. AbdAlhafiz; Nooran S. Elleboudy; Khaled M. Aboshanab; Mohammad M. Aboulwafa; Nadia A. Hassouna (Annals of Clinical Microbiology and Antimicrobials, 2023)
Abstract Background Methicillin-Resistant Staphylococcus aureus (MRSA) causes life-threatening infections, with narrow therapeutic options including: vancomycin and linezolid. Accordingly, this study aimed to characterize phenotypically and genotypically, the most relevant means of linezolid resistance among some MRSA clinical isolates. Methods A total of 159 methicillin-resistant clinical isolates were collected, of which 146 were indentified microscopically and biochemically as MRSA. Both biofilm formation and efflux pump activity were assessed for linezolid-resistant MRSA (LR-MRSA) using the microtiter plate and carbonyl cyanide 3-chlorophenylhydrazone (CCCP) methods, respectively. Linezolid resistance was further characterized by polymerase chain reaction (PCR) amplification and sequencing of domain V of 23 S rRNA; rplC; rplD;and rplV genes. Meanwhile, some resistance genes were investigated: cfr; cfr(B); optrA; msrA;mecA; and vanA genes. To combat LR-MRSA, the effect of combining linezolid with each of 6 different antimicrobials was investigated using the checkerboard assay. Results Out of the collected MRSA isolates (n = 146), 5.48% (n = 8) were LR-MRSA and 18.49% (n = 27) were vancomycin-resistant (VRSA). It is worth noting that all LR-MRSA isolates were also vancomycin-resistant. All LR-MRSA isolates were biofilm producers (r = 0.915, p = 0.001), while efflux pumps upregulation showed no significant contribution to development of resistance (t = 1.374, p = 0.212). Both mecA and vanA genes were detected in 92.45% (n = 147) and 6.92% (n = 11) of methicillin-resistant isolates, respectively. In LR-MRSA isolates, some 23 S rRNA domain V mutations were observed: A2338T and C2610G (in 5 isolates); T2504C and G2528C (in 2 isolates); and G2576T (in 1 isolate). Amino acids substitutions were detected: in L3 protein (rplC gene) of (3 isolates) and in L4 protein (rplD gene) of (4 isolates). In addition, cfr(B) gene was detected (in 3 isolates). In 5 isolates, synergism was recorded when linezolid was combined with chloramphenicol, erythromycin, or ciprofloxacin. Reversal of linezolid resistance was observed in some LR-MRSA isolates when linezolid was combined with gentamicin or vancomycin. Conclusions LR-MRSA biofilm producers’ phenotypes evolved in the clinical settings in Egypt. Various antibiotic combinations with linezolid were evaluated in vitro and showed synergistic effects.